Motivational interviewing in addiction services: an exploratory study of training needs - Wieland, Nuri; Larsen, Helle; Wiers, Reinout W.; Kühling, Julia; Brunner, Wiebke; Frischknecht, Ulrich (European addiction research, 2025)
Introduction: The effectiveness of Motivational Interviewing (MI) in addiction treatment has been proven many times. Many national treatment guidelines throughout the EU recommend MI as a method in the treatment of addiction-related and comorbid disorders. However, little is known on the availability of workforce that is able to provide sufficiently quality-secured MI. The aim of this study was to investigate the level of training and the use of MI among addiction care professionals in Germany. Methods: In a quantitative, anonymous cross-sectional survey, 262 professionals from the addiction care system were asked about their training in MI, their level of knowledge, the motivation of their clients, and the use of MI in practice. All data analyses were carried out using SPSS. Results: Among the professionals, 54.8% (n = 143) reported having had at least 1 day of training in MI. 64.3% (n = 90) of the trained professionals felt sufficiently trained for their area of responsibility. 31.0% (n = 83) of the total sample stated that further training, quality circles, training courses, or similar had been set up at their facility. Results of an ordinal logistic regression indicated that the use of MI in practice could be predicted by MI-specific training (OR = 0.23, 95% CI = 0.13-0.38, p < 0.01) and the availability of MI support structures in the institution (OR = 0.48, 95% CI = 0.28-0.81, p < 0.01). Conclusions: The results suggest a divergence between medical treatment recommendations for the use of MI and the level of training required for this in the German addiction treatment landscape.
Online veröffentlicht: 28. Mai 2025
Gesehen am 26.08.2025